2022
DOI: 10.3390/medicina58020208
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii Infection in Patients with Psychiatric Disorders from Western Romania

Abstract: Background and Objectives: High rates of infection with Toxoplasma gondii were found in psychiatric patients globally. In this study, we assessed for the first time the prevalence of T. gondii infection in psychiatric patients and healthy individuals with no known psychiatric disorders in Western Romania. Materials and Methods: The presence of specific IgG anti-T. gondii antibodies was evaluated in 308 psychiatric patients and 296 control subjects using a chemiluminescence assay. Results: Overall, the seroprev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…For example, T. gondii seropositivity has been associated with schizophrenia due to abnormal dopamine transmission [102] as well as a risk factor for the development of depression and other psychiatric disorders [103]. In addition to dopamine, there was a significantly higher prevalence of anti-T. gondii IgG antibodies among patients in Western Romania with schizophrenia (69.77%), personality/behavior disorders (76.74%), and mental disorders concerning alcohol abuse (84.62%) compared to controls (p = 0.009, p = 0.005, p = 0.043, respectively) [104]. Likewise, substance use is linked to the manipulation of dopamine transmission and the development of these diseases [105].…”
Section: Further Evidence Linking T Gondii Infection and Alcohol Use ...mentioning
confidence: 99%
“…For example, T. gondii seropositivity has been associated with schizophrenia due to abnormal dopamine transmission [102] as well as a risk factor for the development of depression and other psychiatric disorders [103]. In addition to dopamine, there was a significantly higher prevalence of anti-T. gondii IgG antibodies among patients in Western Romania with schizophrenia (69.77%), personality/behavior disorders (76.74%), and mental disorders concerning alcohol abuse (84.62%) compared to controls (p = 0.009, p = 0.005, p = 0.043, respectively) [104]. Likewise, substance use is linked to the manipulation of dopamine transmission and the development of these diseases [105].…”
Section: Further Evidence Linking T Gondii Infection and Alcohol Use ...mentioning
confidence: 99%
“…T. gondii can undergo a transformation into intracellular cysts, residing in organs such as the liver, muscles and neuronal cells, persisting throughout the lifetime of the host. It has also been suggested that a correlation exists between chronic brain infection with T. gondii and alterations in patient neuronal architecture, neurochemistry and behavior ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Limited epidemiological data on the relationship between T. gondii infection and psychiatric diseases were published in Romania. The current literature on this subject did not evaluate the possible contamination routes and risk factors that may be associated with infection in psychiatric patients [ 35 , 36 ]. Therefore, we performed a cross-sectional study in a population of psychiatric patients residing in Arad County, Western Romania, to estimate the prevalence of T. gondii IgG antibodies and to further identify the potential risk factors that may lead to possible infection with this protozoan parasite.…”
Section: Introductionmentioning
confidence: 99%